NURTURING 21ST CENTURY SKILLS THROUGH SERVICE LEARNING: FROM ISOLATION TO CONNECTION - Sivalingam, Parvani; Yunus, Melor Md (PEOPLE: International Journal of Social Sciences, 2017)
As our nation is gearing up towards 21 century learning, herculean measures have been taken to ensure that our students are geared with 21st century skills. One of the key milestone in tailoring our students with 21st century skills is Service Learning (SL). Although SL is incorporated in the education world, the advent of Service Learning concept itself is still relatively new in our region. This quasi-experimental study explored on the effects of service learning on student’s attitude towards learning. The pre and post-survey data shows that service learning has significant positive impact on student’s learning attitude (Mean=10.2, SD=1.74). Concomitantly, service learning has a bright prospect in our country towards honing 21st century skills among our students.